Do vehicle grants and vehicle adaptations grants promote transport mobility and community access for children with difficulties in Sweden? - Sjodin, Linda; Buchanan, Angus; Mundt, Beate; Karlsson, Emelie; Falkmer, Torbjorn (Wiley-Blackwell Publishing Asia, 2012)
Background/aim: A vast majority of the journeys made by children with disabilities in Sweden are in the family car, which usually is bought and adapted for the child with governmental subsidies. Despite the important philosophical views about accessible vehicles, little is known about the impact of vehicle adaptations on families’ lives. The aim of the study was to investigate parent views about the impact of vehicle grants and vehicle adaptation grants on their children’s transport mobility and community access. Methods: In total, 434 parents of children with disabilities in Sweden who had received vehicle grants and/or vehicle adaptation grants between 1998–2007 responded to a questionnaire comprising questions with both pre-selected and open-ended answers. A non-responder analysis was performed. Results: Children with disabilities were found to increase their transport mobility and community access in society as vehicle grants and/or vehicle adaptation grants were given to their parents. Their travel patterns and their travel priorities with their family car indicated that family friends and relatives and leisure activities were frequently visited and prioritised destinations. The grants were linked to access to social and family activities, provided environmental gains and led to increased experienced security. The results also showed that the potential to make spontaneous trips had increased substantially and that families experienced feelings of freedom and enhanced community access. The non-responder analysis confirmed these results. Conclusions: According to parents, vehicle grants and vehicle adaptation grants for children with disabilities have a positive impact on the children’s transport mobility and community access.